Comparison effectiveness of use antihypertensive in preeclampsia patient in RSUD Panembahan Senopati Bantul - Andriana Sari; Wisi Unggul Pertiwi; Faridah Baroroh (Pharmaciana, 2023)
Preeclampsia is one of many unsolved obstetric problems. The purpose of this research is to compare effectiveness of antihypertensive in preeclampsia patient in RSUD Panembahan Senopati Bantul in the period January-July 2019. This study needs to analyze about antihypertensive drugs in preeclampsia because Preeclampsia is the 3rd rank of disease in pregnancy that causes maternal death after hemorrhagic and cardiovascular diseases. The study was conducted at Panembahan Senopati Hospital Bantul because hypertension in inpatient was ranked first in 10 distributions of non-communicable diseases. The research was observational analytic using a cross sectional study with retrospective data collection of patient medical record. Samples were selected on inclusion and exclusion criteria in 46 cases. Data analysis using Mann-Whitney to determine differences in drug effectiveness and Fisher's to determine the relationship. The results are found that no relationship between maternal age, obstetrical age, pregnancy status, method of birth, and length of stay, but there was a relationship between the severity of preeclampsia with the achievement of blood pressure targets. The results of comparative analysis of the effectiveness nifedipine monotherapy with combination of nifedipine + methyldopa there was a significant difference (p = 0.006), and there was a significant relationship between nifedipine monotherapy and combination of nifedipine + methyldopa (p = 0.015) OR results = 7.200. The conclusion of this study is more effective to use the combination of nifedipine + methyldopa for patients with preeclampsia.